Cartilage-specific deletion of Alk5 gene results in a progressive osteoarthritis-like phenotype in mice. Issue 11 (November 2017) - Wang, Q.; Tan, Q.Y.; Xu, W.; Qi, H.B.; Chen, D.; Zhou, S.; Ni, Z.H.; Kuang, L.; Guo, J.Y.; Huang, J.L.; Wang, X.X.; Wang, Z.Q.; et al.
Summary: Objective: Previous studies have shown that Transforming growth factor-β (TGF-β)/TGFβRII-Smad3 signaling is involved in articular cartilage homeostasis. However, the role of TGF-β/ALK5 signaling in articular cartilage homeostasis has not been fully defined. In this study, a combination of in vitro and in vivo approaches was used to elucidate the role of ALK5 signaling in articular cartilage homeostasis and the development of osteoarthritis (OA). Design: Mice with inducible cartilage-specific deletion of Alk5 were generated to assess the role of ALK5 in OA development. Alterations in cartilage structure were evaluated histologically. The expressions of genes associated with articular cartilage homeostasis and TGF-β signaling were analyzed by qRT-PCR, western blotting and immunohistochemistry. The chondrocyte apoptosis was detected by TUNEL staining and immunohistochemistry. In addition, the molecular mechanism underlying the effects of TGF-β/ALK5 signaling on articular cartilage homeostasis was explored by analyzing the TGF-β/ALK5 signaling-induced expression of proteoglycan 4 (PRG4) using specific inhibitors. Results: Postnatal cartilage-specific deletion of Alk5 induced an OA-like phenotype with degradation of articular cartilage, synovial hyperplasia, osteophyte formation, subchondral sclerosis, as well as enhanced chondrocyte apoptosis, overproduction of catabolic factors, and decreased expressions of anabolic factors in chondrocytes. In addition, the expressions of PRG4 mRNA and protein were decreased in Alk5 conditional knockout mice. Furthermore, our results showed, for the first time, that TGF-β/ALK5 signaling regulated PRG4 expression partially through the protein kinase A (PKA)-CREB signaling pathway. Conclusions: TGF-β/ALK5 signaling maintains articular cartilage homeostasis, in part, by upregulating PRG4 expression through the PKA-CREB signaling pathway in articular chondrocytes.